The Role of Age in SLA: A Review of the Literature between 2012-2023 - Ghina Aulia Hasanah; Nasrullah, Nasrullah (LP2M IAIN Sultan Amai Gorontalo, 2023)
Second Language Acquisition (SLA) is a complex process of acquiring a second language after a first language is already established, one of the factors is the age factor. Over the past few years, there has been a lot of study that argued that age plays an important role in learning a second language. Some studies stated that age has been considered a major factor in determining language learners’ success in second language acquisition. There is an assumption that the younger the learner, the better it is for them to acquire a second language. Even so, those studies did not specifically talk about how the role of age has an effect on second language acquisition. Therefore, in order to fill that gap, this study aimed to give some contribution in offering some answers regarding the role of age in second language acquisition. The result of this study indicated that age can be a contributing factor in someone’s second language acquisition. However, it is not the only driving factor since there are still so many variables that can affect one’s ability to acquire a second language.